Syekh Abdurrauf As Singkili dan Transformasi Islam di Kilangan Aceh Singkil, 1611-1675 - Wati, Herlina; Fitri, Hadiani; Sumantri, Pulung (Local History & Heritage, 2023)
This research unveils the historical role of Syekh Abdurrauf As Singkili in the dissemination of Islam in the village of Kilangan, Aceh Singkil, during the period of 1611-1675, utilizing a four-step historical research method. The primary research focuses encompass the process of Islam propagation, Syekh Abdurrauf As Singkili's contributions to Islam in the region, and the community's perception of him in the context of religious dissemination. The historical research method involves four stages: heuristics, criticism, interpretation, and historiography. Subsequently, data analysis is conducted to delineate Syekh Abdurrauf As Singkili's role in spreading Islam in Aceh Singkil. The research highlights Syekh Abdurrauf As Singkili's significant role in disseminating Islam through teaching his disciples and establishing an Islamic school in Aceh Singkil. The local community holds him in high regard, acknowledging his pivotal role in the proliferation of Islam in the region. This study illustrates the substantial impact of Syekh Abdurrauf As Singkili's role on the development of Islam in Aceh Singkil.